IMRT technique in patients with breast cancer treated with breast conserving therapy – obstacles and advantages - Ziółkowska, Ewa; Wiśniewski, Tomasz; Kubiak, Maria; Zarzycka, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2007)
Breast cancer is the most frequently occurring type of malignant tumour in women in Poland. About 12 thousand new cases of breast cancer are registered annually, among which the greater part (70-80%) is represented by women in the early phase of the disease. Conserving therapy is the standard approach in early breast cancer. The role of radiotherapy as a supplement to surgical treatment is also underlined. For over 100 years radiotherapy has been one of the basic methods to treat patients with malignant tumour of the breast. Nowadays the use of ionizing radiation has become an integral method of the multidisciplinary and modern treatment of patients with breast cancer after conserving surgery. Within the last few years the improvement of radiotherapy techniques has been observed to correct the therapeutic index of radiation. The modulation of the intensity of the beam (intensity modulated radiation therapy, IMRT) is a new method of radiotherapy which assures delivery of the highest possible radiation dose into the area of the tumour with the simultaneous maximum protection of healthy tissues. The purpose of this study is to set out the present state of knowledge on possibilities of using the technique of IMRT on patients with breast cancer after conserving therapy. In the article available literature is reviewed and an analysis of the advantages and disadvantages of using IMRT in breast cancer compared to standard conformal techniques is presented.